Psychometric properties of the Persian version of the Cultural Competence Scale in Clinical Nurses - Naeimeh Sarkhani; Reza Negarandeh; Raziyeh Dashti (Wiley, 2022)
Abstract Aim Cultural competence is a crucial component of nursing competency, and a valid and reliable scale is needed to measure it. This study was conducted to investigate the psychometric properties of the Persian version of the Cultural Competence Scale among Iranian clinical nurses. Design A methodological design was used. Methods The scale was translated into Persian, and its content, face and construct validity, and reliability were examined. Results Two items with a content validity ratio of 0.6 were removed. In the case of the content validity index, one item with a content validity index lower than 0.70 was removed. The mean content validity index for the scale was reported as 0.99. All 31 items with an impact score index higher than 1.5 were approved. The exploratory factor analysis revealed four factors explaining 59.92% of the total variance. Cronbach's alpha and the intraclass correlation coefficient were calculated at 0.95 and 0.94, respectively.